2021
DOI: 10.1002/anie.202110243
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Origin of Sulfur‐Doped Fe‐N‐C Single‐Atom Catalyst for Enhanced Oxygen Reduction Activity: Effect of Iron Spin‐State Tuning

Abstract: Heteroatom doped atomically dispersed Fe 1 -NC catalysts have been found to show excellent activity toward oxygen reduction reaction (ORR). However,t he origin of the enhanced activity is still controversial because the structurefunction relationship governing the enhancement remains elusive.Herein, sulfur(S)-doped Fe 1 -NC catalyst was obtained as amodel, which displays asuperior activity for ORR towards the traditional Fe-NC materials. 57 Fe Mçssbauer spectroscopy and electron paramagnetic resonance spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
161
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(169 citation statements)
references
References 35 publications
8
161
0
Order By: Relevance
“…After adsorption of HOO*, there are two single electrons in the d yz d xz and d z 2 orbits for Co of pyrrole-type CoN 4 , while the electrons are paired in Co of pyridine-type CoN 4 . It is reported that the high spin state is associated to the weaker adsorption of the HOO* intermediate relative to the low spin state. , Therefore, after adsorption of HOO*, the pyrrole-type CoN 4 showing a high spin state facilitate the HOO* desorption to generate H 2 O 2 . However, the pyridine-type CoN 4 with the low spin state tends to dissociate the O–O bond in HOO* and, lastly, form H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…After adsorption of HOO*, there are two single electrons in the d yz d xz and d z 2 orbits for Co of pyrrole-type CoN 4 , while the electrons are paired in Co of pyridine-type CoN 4 . It is reported that the high spin state is associated to the weaker adsorption of the HOO* intermediate relative to the low spin state. , Therefore, after adsorption of HOO*, the pyrrole-type CoN 4 showing a high spin state facilitate the HOO* desorption to generate H 2 O 2 . However, the pyridine-type CoN 4 with the low spin state tends to dissociate the O–O bond in HOO* and, lastly, form H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic reactions involving triplet-state O 2 molecules have been one of the hottest research topics nowadays. Aqueous-phase oxygen evolution reaction (OER) is a significant component of the oxygen-involved catalytic reactions. , However, it is hampered by its sluggish kinetics owing to the complex four-electron process, which is typically recognized as the bottleneck for water splitting. In principle, the formation of the O–O bond requires the destruction of two O–H bonds, involving the spin-electron evolution of the diamagnetic hydroxides to be oxidized into the paramagnetic oxygen molecules. As a result, the regulation of the spin-state behavior of catalysts would play a considerable role in the OER process. Although the spin-related OER enhancement has already been observed, it has rarely been systematically and comprehensively demonstrated. Therefore, spintronic electrocatalysis is still a relatively blank field of catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the potential mechanism of S doping to improve catalytic activity was proposed from the perspective of theoretical calculations. Chen et al 55 prepared an atomically dispersed S-doped Fe 1 -NC catalyst, and it showed excellent ORR activity with an E 1/2 of up to 0.85 V ( vs. RHE) in 0.1 M KOH solution. Based on the Fe Mössbauer spectrum and electron paramagnetic resonance spectrum (Fig.…”
Section: Heteroatom-doped M–n–c Sacs For the Orrmentioning
confidence: 99%